The Influence of Sharia Financial Literacy, Service Quality, Promotion, and Religiosity on Customer Decisions: A Case Study of BSI Lhokseumawe - Baharuddin Ali Tanjung; Muhammad Hafizh (Komunitas Dosen Indonesia, 2025)
This study aims to analyze the influence of Islamic financial literacy, service quality, promotion, and religiosity on customer decisions to use Islamic banking products (a case study of BSI Lhokseumawe City). The research method used is a quantitative descriptive approach. The population of this study was 143,635 customers, with a sample of 100 customers using a purposive sampling formula. Research instruments with validity tests, reliability tests, classical assumption tests with normality tests, multicollinearity tests, and heteroscedasticity tests using IBM SPSS 27. The results of the study show that Islamic financial literacy has a positive and significant effect on decisions of (3.976 > from the t table of 1.985) sig.0.000 < 0.05.Service quality does not have a positive and significant effect on decisions (t count 1.389 < t table 1.985) sig. (0.168 > 0.05. Promotion has a positive and significant influence on customer decisions (t count 4.727 > t table 1.985), sig. (0.000 < 0.05). Religiosity has a positive and significant effect on decisions (t count 4.476 > t table 1.985), sig. 0.000 <0.05. Simultaneously, Islamic financial literacy, service quality, promotion, and religiosity have a positive and significant influence on decisions (F count 119.476 > F table 2.467), sig. 0.000 <0.05.